"Stutter-Stop Flash-Bulb Strange": GMOs and the Aesthetics of Scale in Paolo Bacigalupi's The Windup Girl. - Selisker, Scott (Science Fiction Studies, 2015)
This article raises questions about the aesthetics of scale as they appear relative to genetically modified organisms in science fiction and especially in Paolo Bacigalupi's The Windup Girl (2009). Bacigalupi makes the unusual choice of representing GMOs largely through science-fictional tropes of automatism rather than the grotesque. Because of this choice, The Windup Girl inventively enables readers to relate to the very small spatial scales and the long temporal scales at which the genome and its effects are most visible. The article suggests that science fiction has particular flexibility with the aesthetics of scale, particularly where technoscientific phenomena have profound consequences that take place at nonhuman scales.